Supply chain control towers: Technology push or market pull—An assessment tool - Patsavellas, John; Kaur, Rashmeet; Salonitis, Konstantinos (Wiley on behalf of IET, 2021)
As digital technology and connectivity advance rapidly, the premise of bringing supply chain (SC) visibility across multiple tiers of supply, whilst facilitating the velocity to achieve strategic business objectives, is gaining interest. The feasibility and timing for successful adoption and implementation of such technology depend primarily on the readiness level and specific needs of each organisation, making it imperative to exercise insightful judgement as it can be expensive to acquire, develop and master. This research study examines the market pull versus technology push components of the functionalities enabled by digital SC control towers and buildings on the outcome of an extensive survey and expert interviews and proposes an assessment tool to aid decision making for the consideration of their adoption.
Keywords: computer integrated manufacturing; decision making; manufacturing industries; manufacturing systems; supply chain control towers